2003
DOI: 10.1161/01.hyp.0000080495.07301.31
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Control of Muscle Sympathetic Nerve Activity After Carotid Body Tumor Resection

Abstract: Abstract-Bilateral carotid body tumor resection causes a permanent attenuation of vagal baroreflex sensitivity. We retrospectively examined the effects of bilateral carotid body tumor resection on the baroreflex control of sympathetic nerve traffic. Muscle sympathetic nerve activity was recorded in 5 patients after bilateral carotid body tumor resection (1 man and 4 women, 51Ϯ11 years) and 6 healthy control subjects (2 men and 4 women, 50Ϯ7 years). Baroreflex sensitivity was calculated from changes in R-R inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
2
18
2
2
Order By: Relevance
“…More importantly, it has been shown that both baroreceptor populations operate over the same range of arterial pressures . Although these studies have several limitations that are inherent in human experimental investigations, the findings are in general agreement with studies in patients who have undergone bilateral carotid sinus denervation, with the collective results demonstrating the importance of the carotid baroreceptors in the reflex control of ABP (Smit et al 2002;Fadel et al 2003;Timmers et al 2003).…”
Section: Figuresupporting
confidence: 81%
“…More importantly, it has been shown that both baroreceptor populations operate over the same range of arterial pressures . Although these studies have several limitations that are inherent in human experimental investigations, the findings are in general agreement with studies in patients who have undergone bilateral carotid sinus denervation, with the collective results demonstrating the importance of the carotid baroreceptors in the reflex control of ABP (Smit et al 2002;Fadel et al 2003;Timmers et al 2003).…”
Section: Figuresupporting
confidence: 81%
“…In contrast, less than complete sinus denervation decreases baroreflex sensitivity and increases MAP variability but does not result in an elevated MAP (59,64). These observations differ from animal studies that show no chronic effect of carotid sinus denervation on either the level of MAP or the variability of MAP (33,45,56).…”
Section: Baroreceptor Denervation: Human Observationscontrasting
confidence: 64%
“…However, the variability of MAP was elevated relative to normal in all four patients at times ranging from 3 mo to 2 yr after surgery. Timmers et al (64) recorded muscle SNA and HR responses to administration of vasoactive drugs in a group of patients who had bilateral carotid body resection 4 -20 years earlier. At the time of the study, none of the patients showed signs of baroreflex failure or were hypertensive, but all showed decreased baroreflex control of HR compared with age-matched controls.…”
Section: Baroreceptor Denervation: Human Observationsmentioning
confidence: 99%
“…However, patients having had bilateral glomus tumor removal are not able to regulate blood pressure adequately, suggesting that aortic baroreceptors may not be able to substitute for carotid sinus baroreceptors. 32 Continuous radial artery blood pressure recordings calibrated on oscillometric brachial artery measurements were used to determine carotid distensibility. Whether peripheral blood pressure measurements introduce uncertainty in computing carotid distensibility is quite unlikely, although we have to acknowledge that differences between peripheral and central arterial pulse waves might occur.…”
Section: Discussionmentioning
confidence: 99%